1998
DOI: 10.1111/j.2042-7158.1998.tb03358.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Efficacy of Free and Non-ionic-surfactant Vesicular Formulations of Paromomycin in a Murine Model of Visceral Leishmaniasis

Abstract: Non-ionic-surfactant vesicular (NIV) formulations of paromomycin have been tested in-vitro and in-vivo for their activity against Leishmania donovani. Production of NIV was dependent both on the surfactant used and on the concentration of paromomycin; only two of the surfactants studied formed vesicles at the highest paromomycin concentration (9 mg mL(-1)). At surfactant-lipid concentrations > or = 1.5 mM, suspensions of NIV (drug- or glucose-loaded) were cytotoxic to macrophages infected with L. donovani; hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…Studies are under way to The results of this study showed that the SSG-NIV was more effective than free SSG both in vitro and in vivo. In vitro studies showed that PBS-NIV did have antileishmanial properties, which confirms results of previous studies (21). However, treatment with PBS-NIV did not significantly suppress parasite burdens in vivo, a finding which was obtained in previous studies (22).…”
Section: Discussionsupporting
confidence: 81%
“…Studies are under way to The results of this study showed that the SSG-NIV was more effective than free SSG both in vitro and in vivo. In vitro studies showed that PBS-NIV did have antileishmanial properties, which confirms results of previous studies (21). However, treatment with PBS-NIV did not significantly suppress parasite burdens in vivo, a finding which was obtained in previous studies (22).…”
Section: Discussionsupporting
confidence: 81%
“…Williams et al (47) strated parasite clearance only from the liver of L. donovaniinfected mice, with single-or double-dose treatment with nonionic-surfactant vesicular formulations of PM (47). Recently, liposomal formulations of PM were used as a topical treatment against CL to show the enhanced skin permeation and retention capacity of PM (10,24).…”
Section: Discussionmentioning
confidence: 99%
“…Unentrapped drug was washed with PBS through ultracentrifugation at 1,00,000 ϫ g for 1 h. PC-SA (22 mg) with entrapped PM was finally resuspended in PBS. The entrapped PM concentration was determined by an agar diffusion inhibition assay of the growth of Staphylococcus aureus (ATCC 6571) on sensitivity test agar as described previously (47). A straight-line relationship was obtained between PM concentration and zone of inhibition (mm).…”
Section: Methodsmentioning
confidence: 99%
“…Mice treated intravenously were dosed on day 7 with one of the following: PBS (controls), paromomycin (20 mg/kg), SSG solution (300 mg of Sb v /kg), AMB deoxycholate (Fungizone; 0.375 mg of AMB/kg), or liposomal AMB (AmBisome; 8 mg of AMB/kg). A dose of 20 mg of paromomycin/kg was chosen, since previous studies have shown that this dose causes 50% suppression of liver L. donovani parasite burdens (29). AmBisome and Fungizone were prepared in accordance with the manufacturer's instructions and were diluted prior to use with 5% dextrose to give a final AMB concentration of 1 mg/ml.…”
Section: Methodsmentioning
confidence: 99%